Применение метода регуляризации Тихонова при расчете обтекания телесных компоновок летательных аппаратов потоком идеальной жидкости - Калкаманов, С. А. (НТУ "ХПИ", 2004)
It is offered to apply Tikhonov's regulation method to maintenance of tasks decision stability of volumetric bodies flow of an ideal liquid stream. As an example there is shown calculated results of sphere and helicopters body flow
Keywords: решение задач; метод сопряженных градиентов; погрешности аппроксимации; интегральное уравнение; константа